2016
DOI: 10.1111/jors.12281
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Local Spatial Heterogeneities in Housing Market Studies

Abstract: We adopt a novel method to deal with omitted spatial heterogeneities in hedonic house price analysis. A Gaussian variant of the conditional autoregressive (CAR) model is used to study the impact of spatial effects. In a general linear modeling framework, we include zone‐specific random effects that are allowed to interact spatially with neighboring zones. The results demonstrate that this estimator accounts for missing spatial information, producing more reliable results on estimated spatially related coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
(73 reference statements)
1
15
0
1
Order By: Relevance
“…Indeks Moran digunakan untuk mempelajari sejauh mana ukuran interaksi spasial dan kualitas lingkungan berkontribusi untuk spatial smoothing (Osland, Sandvig, & Thorsen, 2016). Indeks Moran (𝐼) merupakan parameter autokorelasi spasial yang dinyatakan sebagai:…”
Section: Indeks Moranunclassified
“…Indeks Moran digunakan untuk mempelajari sejauh mana ukuran interaksi spasial dan kualitas lingkungan berkontribusi untuk spatial smoothing (Osland, Sandvig, & Thorsen, 2016). Indeks Moran (𝐼) merupakan parameter autokorelasi spasial yang dinyatakan sebagai:…”
Section: Indeks Moranunclassified
“…The scalar s reflects the general variance of the random effects. As pointed out by Osland et al (2016), the model is 'improper' because the covariance matrix of the simultaneous distribution is not positive definite. However, it is still being used (Gschl€ oßl and Czado, 2007).…”
Section: A Conditional Autoregressive Spatial Model Formulationmentioning
confidence: 99%
“…First, we account for local spatial interdependencies in a rich and flexible way using a spatial conditional autoregressive (CAR) modelling framework, which includes spatially correlated random effects. Osland et al (2016) have demonstrated that this modelling approach largely adjusts for missing information on spatial characteristics, and contributes considerably to more accurate predictions of house prices. This is particularly so for heterogeneous urban areas, where controlling for omitted spatial variables is highly important.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, the model can also be estimated without this component. In such case, the Wy element can be omitted and the model obtained in this situation would be equal to the HLM model (Hierarchical Linear Model) [60], although HSAR fits a simultaneous autoregressive (SAR) spatial random effect rather than a conditional autoregressive (CAR) spatial random effect.…”
Section: Theoretical Basic Of Conducted Researchmentioning
confidence: 99%